Thermal tipping points in mediterranean mussel adhesion: molecular mechanisms and mechanical consequences of heatwave on byssus production in Mytilus galloprovincialis - Antonina De Marco; Vito Antonio Baldassarro; Corinne Quadalti; Valentina Burato; Laura Calzà; Luciana Giardino; Devis Montroni; Giuseppe Falini; Gabriela Graziani; Nicolas Greggio; Francesco Dondi; Maria Giulia Ferrari; et al. (Scientific Reports)
Abstract Prolonged marine heat waves are a major manifestation of climate change, threatening marine biodiversity. Using the Mytilus galloprovincialis mussel as a sentinel organism, we investigated the impact of experimental, prolonged high temperatures as expected in 2050 on byssus-producing organ. We demonstrated that 30 days exposure at 28 °C, alters molecular and functional properties of mussel foot. Results revealed severe downregulation in the synthesis of the proximal, distal and non-gradient pre-collagen byssus components. The stressed mussels produced less than half the number of byssus filaments compared to the control. Byssus threads showed reduced mechanical resistance to traction, with a 55% decrease in maximum force. At the organism’s health status level, a long-term collapse in heat shock protein 70 subspecies expression suggests energy depletion. This is confirmed by a reduction of the hepatosomatic index during exposure and by the physiological impairment with clearance rate reduction and loss of air exposure tolerance. These effects compromise the mussel’s substrate adhesion, increasing the risk of detachment but also threaten bivalve survival. The potential consequences at the ecological level could be severe, including a reduction in coastal biodiversity, in the ecosystem services provided by these animals, as well as risks to the sustainability of Mediterranean mussel farming.